Glypturus ferox, a new species of ghost shrimp (Decapoda: Axiidea: Callichiridae) from the Ryukyu Islands, southwestern Japan - Sato, Taigi; Komai, Tomoyuki; Shimizu, Naoto (Zootaxa, 2024)
The callichirid ghost shrimp genus Glypturus Stimpson, 1866 was represented until now by four extant species world-wide. Only G. armatus A. Milne-Edwards, 1870 is known from the western Pacific. In this study, we describe G. ferox n. sp. based on seven specimens collected from the Ryukyu Islands, southwestern Japan. All specimens of the new species were collected in inner reef lagoons by suction pump. The new species is easily distinguished from all other congeners, including fossil taxa, by having a row of spines on the lower margin of the major cheliped palm. Molecular phylogenetic analysis using the mitochondrial 16S rRNA gene suggests that G. ferox n. sp. is sister to G. armatus; the genetic divergence between the two species is high. An identification key to extant species of Glypturus is provided. A brief overview on Japanese species of Callichiridae is also provided. Glypturus ferox n. sp. is the nineth species of the family known from Japanese waters with certainty.